Virological activity in treatment-naïve HBeAg-negative HBV-infected adult patients: A community-based study in Jiangsu, China. Issue 29 (17th July 2020) - Zhai, Xiangjun; Zhu, Liguo; Jiang, Jie; Song, Ci; Peng, Hong; Qian, Jiao; Zhou, MingHao; Zhou, Yan; Wang, Qungang; Xu, Jianfang; Wang, Zhijian; Liu, Hongjian; et al.
Abstract : Abstract: Nowadays most of the hepatitis B virus (HBV) infected population are adults, among which hepatitis B e antigen (HBeAg) negative infection occupied the largest proportion of HBV infection in China. HBeAg-negative patients are heterogeneous, and the corresponding interventions are different. Therefore, it is worth researching the infection characteristics of HBeAg-negative patients to help guide the interventions. A total of 11, 738 treatment-naïve HBeAg-negative adult patients were randomly selected, and their demographic and medical history information were collected. The liver biochemistry, and HBV infection biomarkers including hepatitis B surface antigen (HBsAg), hepatitis B surface antibody (anti-HBs), HBeAg, hepatitis B e antibody (anti-HBe), hepatitis B core antibody (anti-HBc), and hepatitis B virus deoxyribonucleic acid (HBV-DNA) levels were tested. The infection characteristics and their influencing factors were explored. Sixty percent of the patients presented HBV-DNA-positive, of which 31.2% had HBV-DNA level higher than 2000 IU/mL, and 16.5% had HBV-DNA level higher than 20, 000 IU/mL. HBV-DNA levels tended to increase along with the increasing of age, and the male patients had significant higher HBV-DNA levels than the female patients. Twenty-four percent of the patients had abnormal transaminase. The male patients were more vulnerable to abnormal transaminase (30.0%) than the female patients (18.4%). Fifty-five percent patients with HBV-DNA ≥20, 000 IU/mL presented abnormal alanine aminotransferase (ALT) or aspartate transaminase (AST), which was significantly higher than that of patients with HBV-DNA levels below 20, 000 IU/mL (19.0–21.7%). Multivariate logistic regression analyses revealed that the male patients and the patients with higher viral load had higher risk of having abnormal liver function. A considerable number of HBeAg-negative patients were virological active and had liver damage. It is necessary and urgent to carry out regular active interventions for the chronic HBV-infected patients.